Clinical effect of platelet rich fibrin in the treatment of periodontal intrabony defects. Systematic review and meta-analysis - Arbildo, H. (2017)
Background: There is currently no gold standard biomaterial for the treatment of periodontal intrabony defects (PIDs). One of the current options is the use of platelet-rich fibrin (PRF). Objective: To determine the clinical effect of PRF in the treatment of PID through a systematic review and meta-analysis. Materials and Methods: A literature search was conducted up to February 2017 in the following biomedical databases: Pubmed, Embase, Scielo, Science Direct, SIGLE, LILACS and in the Cochrane Central Register of Clinical Trials. The selection criteria included: randomized clinical trials published in the last 5 years, reporting clinical effects (probing depth, clinical insertion level or gingival recession), with a follow-up time equal to or greater than 6 months, and sample size larger than or equal to 10 patients reporting the use of PRF as a treatment for PID. The methodological quality of the studies was analyzed using the Cochrane Handbook of Systematic Reviews of Interventions as a reference. Results: The search strategy yielded 20 articles. A reduction in probing depth and an increase in clinical insertion level or a reduction in gingival recession is reported, when using PRF alone or in combination with another biomaterial or substance that stimulates tissue regeneration. Conclusion: The literature suggests that the use of PRF in the treatment of PIDs has a beneficial clinical effect when compared to control treatments. © 2017, Universidad de Concepcion. All rights reserved.